2021
DOI: 10.1155/2021/8453726
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Vehicle Trajectory Prediction for Traffic Conflict Detection at Unsignalized Intersections

Abstract: Real-time prediction of vehicle trajectory at unsignalized intersections is important for real-time traffic conflict detection and early warning to improve traffic safety at unsignalized intersections. In this study, we propose a robust real-time prediction method for turning movements and vehicle trajectories using deep neural networks. Firstly, a vision-based vehicle trajectory extraction system is developed to collect vehicle trajectories and their left-turn, go straight, and right-turn labels to train turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The method of CA-UKF, CS-UKF, and CS-CKF (this paper proposed) models are applied to track and predict the vehicle maneuvering state. As the intersection is a high incidence place of traffic accidents, tracking the vehicle trajectory in the intersection has more practical importance [22]. We selected the intersection of Yingbin Avenue crossed Qiche Avenue in Nanchang as the research object.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…The method of CA-UKF, CS-UKF, and CS-CKF (this paper proposed) models are applied to track and predict the vehicle maneuvering state. As the intersection is a high incidence place of traffic accidents, tracking the vehicle trajectory in the intersection has more practical importance [22]. We selected the intersection of Yingbin Avenue crossed Qiche Avenue in Nanchang as the research object.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Where Yi is the anticipated position of the vehicle at time step i, Yi* is the equivalent ground truth position, and N is the number of time steps in the predicted trajectory. Previously discussed models CNN_Raw-RNN [38], Four layer LSTM [40] and U net (6 layer) [43] have achieved MAE values are 0.113, 0.29 and 0.38 in meters respectively. We observed that CNN_Raw-RNN [38] has a less MAE value when compared with other models which indicate that it better performed.…”
Section: B Performance Evaluation Analysis Of Trajectory Planning Met...mentioning
confidence: 95%
“…In addition, to detect traffic conflicts at unsignalized crossings, Qianxia Cao et. al [40] have developed a real-time vehicle trajectory estimation technique. To forecast each vehicle's upcoming motion as it approaches an intersection, the system employs a DL-based method.…”
Section: B Detailed Survey On Dl-based Trajectory Planning For Sdvmentioning
confidence: 99%
“…The encoder module is used for hidden layer vector computation. The obtained vehicle trajectory information x, y can be extracted into the LSTM encoder after being processed by increasing the dimension [7]. For any time point t, its motion and trajectory information can be expressed as Equation 10.…”
Section: Lstm Encodermentioning
confidence: 99%